Study of forming features of human capital of oil and gas companies of Ukraine - Ревтюк, Є. А. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article focuses on statistics on training and retraining of specialists for Ukrainian oil and gas industry in IFNTUOG. The dynamics of employment of university graduates were analyzed in terms of professions, and in the context of the largest companies of the industry. The provision of the internship positions for university students by the major enterprises was also studied. The article reveals the basic trends of human capital formation in oil and gas industry of the country.